Konsep Kepemilikan Harta Sebagai Bagian Hak Asasi Ekonomi Perspektif Al-Qur’an - Syamsiah Muhsin; Achmad Abu Bakar; Halimah Basri (Al-Azhar Journal of Islamic Economics, 2022)
This article describes the concept of property ownership as part of human economic rights and also describes how the Qur'anic insights about the concept of property ownership. This research is a qualitative descriptive study using a library research approach. Sources of data in this study using primary and secondary data sources. The technique of collecting data is by keyword searching, subject searching and from the latest scientific articles. Data checking is done by triangulation technique. The results of the study found that (1) Property ownership is one part of the concept of economic rights that is recognized and protected by law. Islamic economics distinguishes the concept of Islamic ownership from the concept of ownership in countries that adhere to both capitalist and socialist systems. (2) Islam as a Shari'a highly upholds economic rights which include property rights. Allah explains about property ownership in the Qur'an that humans are given the right by Allah to manage and own property as a gift and mercy from Allah. This is an affirmation for humans that Allah is the owner of everything in the heavens and on earth. Keywords: Concept of Property Ownership, Economic Human Rights, Qur’anic Perspective Abstrak Artikel ini memaparkan tentang konsep kepemilikan harta sebagai bagian dari hak asasi ekonomi manusia juga memaparkan bagaimana wawasan Al-Quran tentang konsep kepemilikan harta. Penelitian ini merupakan penelitian deskriptif kualitatif menggunakan pendekatan riset kepustakaan. Sumber data dalam penelitian ini menggunakan sumber data primer dan sekunder. Tehnik pengumpulan data dengan pencarian kata kunci, pencarian subyek dan dari artikel ilmiah terkini.Pengecekan data dilakukan dengan tehnik triangulasi. Hasil penelitian ditemukan bahwa (1) Kepemilikan harta adalah salah satu bagian dari konsep hak asasi ekonomi yang diakui dan dilindungi pelaksanaannya oleh Undang-undang. Ekonomi Islam membedakan konsep kepemilikan Islam dengan konsep kepemilikan pada negara yang menganut sistim kapitalis maupun sosialis. (2)Islam sebagai suatu syariat sangat menjunjung tinggi hak asasi ekonomi yang didalamnya mencakup tentang hak kepemilikan harta. Allah menjelaskan tentang kepemilikan harta dalam Al-Quran bahwa manusia diberi hak oleh Allah untuk mengelola dan memiliki harta sebagai karunia dan rahmat dari Allah. Hal ini menjadi penegasan bagi manusia bahwa Allah adalah pemilik segala sesuatu di langit dan di bumi. Kata Kunci: Konsep Kepemilikan Harta, Hak Asasi Ekonomi, Perspektif Al-Quran